Digital Library Using Green Stone: A Study - Krishnamurthy, M. (Journal of Information and Knowledge, 2014)
Automation at ISIBC library started with the use of CDS/ISIS and Libsys. Now it has started GSDL to create digital collections. Digitization is becoming a major consideration for all library and information services. This paper outlines the practical issues and key stages involved in digitizing ISIBC in-house documents, based on work undertaken as part of the digitization of in-house volumes, aims to develop a working model of the hybrid library with a teaching and research context. Having selected the material to be digitized, a feasibility study needs to be undertaken to gauge whether it is actually viable to undertake the digital imaging study.